LBOS 02-03 THE INFILTRATING MACROPHAGE-SECRETED GALECTIN-3 PLAYS AN ESSENTIAL ROLE IN CARDIAC FIBROSIS AND DIASTOLIC FUNCTION IN MURINE PRESSURE-OVERLOAD MODEL. (September 2016) - Chen, Jin-jer; Hao, Wen-Rui; Chang, Kuan-Cheng; Liu, Ju-Chi
Abstract : Objective: Cardiac fibrosis is the major pathophysiological process, contributing to the development of diastolic heart failure. We examine the role of macrophage-derived galectin-3 (gal-3) in cardiac fibrosis and diastolic function in response to transverse aortic constriction (TAC). Design and method: wild-type (WT) and gal-3 knock-out (KO) mice subjected to TAC; immunohistochemistry for myocardial macrophage infiltration, gal-3, and CTGF (connective tissue growth factor) expression; picrosirius red stain for myocardial fibrosis; FACS flow- cytometry for defining the origin of myocardial macrophages. MTT and Brdu incorporation for cell proliferation; flow-cytometry for cell differentiation; co-immunoprecipitation and confocal microscopy for lectin-carbohydrate interaction and co-localization respectively; echocardiography for left ventricular function. Results: WT mice after TAC showed significant increase of myocardial macrophage infiltration, gal-3 and CTGF expression, fibroblast proliferation/differentiation, and interstitial fibrosis leading to diastolic dysfunction, compared with controls (n = 10, p < 0.01). FACS flow-cytometry further identified that the increased myocardial macrophage population contains predominantly MHC-II low CCR2+ monocytes and MHC-II high CCR2+ monocyte-derived macrophages. Macrophage depletion or gal-3 Knock-out mice markedly suppressed myocardial fibrosis. Re-administration of macrophages restored the fibrosis. In in-vitro, confocal microscopy and co-immunoprecipitation confirmed co-localization and gal-3-EGFR interaction on cell membrane. Treatment with recombinant gal-3 increased EGFR and downstream ERK phosphorylation, and CTGF expression in wild-type or gal-3 knock-down fibroblasts. Moreover, using MTT and Brdu incorporation assays, addition of gal-3, or macrophage-derived supernatant, or co-culture with macrophages significantly promoted fibroblast proliferation via CTGF expression. Finally, administration of gal-3 neutralizing monoclonal antibody remarkably reversed the myocardial fibrosis and improved diastolic function. Conclusions: Pressure-overload promotes myocardial macrophage infiltration and the macrophage -secreted gal-3 cross-links with its glycoconjugate, EGFR, resulting in its autophosphorylation, activation of subsequent mitogenic ERK signaling, myocardial CTGF expression, fibroblast proliferation/differentiation, resulting in myocardial fibrosis and diastolic dysfunction. Our findings provide molecular basis for gal-3 as a promising therapeutic target in heart failure.